Socio-psychological research of value orientations of students - Evgeniia L. Chernyshova; Dmitry V. Ivanov; Ekaterina I. Roschupkina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The analysis of philosophical, sociological, pedagogical and psychological literature let us make a conclusion that the fundamental basis of the legal consciousness of each person is the degree of his spiritual perfection and maturity. Value and spiritual and moral prerequisites, in turn, are the basis of law, making the behavior of an individual in society expedient. The authors of the paper focus their attention on the frequent cases of delinquent behavior among young students. There is a new form of delinquent behavior, that is deviant socio-political activity. The authors of the paper see the problem of contradiction between the real state of legal consciousness of students and the lack of knowledge of the relationship of legal consciousness with individual psychological characteristics and value orientations of students. The desire to find ways to resolve this contradiction determined the purpose of the research conducted to investigate the relationship of legal consciousness with individual psychological characteristics and value orientations of Samara students who took part in unauthorized protest actions in January 2021. The paper presents the results of an empirical study of individual psychological characteristics and value orientations of students who took part in unauthorized protest actions. The results received, it was found that the subjects of the sample are really prone to delinquent behavior, they have a low level of volitional control of the affective sphere, a pronounced tendency to aggression and violence against the background of negative attitudes towards social norms and rules, the level of legal awareness is low, a positive attitude to law is not formed, and higher, spiritual values are rejected. Among the preferred values are the values of the hedonistic and gloric vector.